An informed approach to the development of primary care pediatric firearm safety messages - Lindsay N. Fuzzell; Sherry Dodd; Sisi Hu; Amanda Hinnant; Sungkyoung Lee; Glen Cameron; Jane M. Garbutt (BMC, 2022)
Abstract Background Firearm ownership is prevalent in the US and many children spend time in areas where firearms are not stored safely. The AAP recommends firearm safety counseling at pediatric well-visits. Methods We developed and tested six contextual messages to promote safe firearm storage based on: absence of harm, collective appeal to understanding child behavior, pediatrician's authority, evidence-based, fear appeal, and general safety considerations. One hundred four parents who keep firearms at home were recruited from Amazon Mechanical Turk Prime and viewed video messages and reported behavioral intentions and emotional reactions following each message. Results All six contextual messages were perceived as important and believable and increased parents' intentions to follow safety advice provided, but also elicited negative emotions. The authority message elicited more negative emotions and resulted in lower intentions to follow safe storage advice. Conclusions Including firearm messages with other child safety advice merits further evaluation. Authority messages should be avoided.